Arte, sociedad y consumo actual metamorfosis cultural alimentaria en el contexto local. - Cruz Castro, Marco Valerio (2015)
Classic, beautiful and the need for the new feed investigation processes - generating production work in different periods or stages, and also give validity and relevance of art, design and culture of this country. The definition of content helps artists designing various proposals and designs that help society become aware, through painting can show the needs, thoughts and expressions. All this, as a contribution to improve the conditions for coexistence, communication, appreciation and human expression through the various expressions of the image and its languages. We can see from academia, such as art and design meet to get a project whose aim is to obtain a degree as is the degree. Reference to the above, this project presents a proposal to capture through art and design, food with the Machaleña population, with a vision to change the eating habits of the citizens.